2021
DOI: 10.1007/s00586-021-07067-w
|View full text |Cite
|
Sign up to set email alerts
|

Laminectomy alone versus laminectomy with fusion for degenerative cervical myelopathy: a long-term study of a national cohort

Abstract: Purpose To compare patient-reported 5-year clinical outcomes between laminectomy alone versus laminectomy with instrumented fusion in patients with degenerative cervical myelopathy in a population-based cohort. Methods All patients in the national Swedish Spine Register (Swespine) from January 2006 until March 2019, with degenerative cervical myelopathy, were assessed. Multiple imputation and propensity score matching based on clinicodemographic and radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In a two-year follow-up study, conventional laminectomy with instrumented fusion and laminectomy alone in degenerative cervical myelopathy (DCM) revealed similar effectiveness [ 18 ]. Dios compared patient-reported 5-year clinical results between conventional laminectomy alone and laminectomy with instrumented fusion in patients with DCM and found no important differences [ 19 ]. A recent narrative review concluded that conventional laminectomy alone was an effective treatment without the additional risks of posterior instrumentation in highly selected patients with normal preoperative cervical sagittal alignment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a two-year follow-up study, conventional laminectomy with instrumented fusion and laminectomy alone in degenerative cervical myelopathy (DCM) revealed similar effectiveness [ 18 ]. Dios compared patient-reported 5-year clinical results between conventional laminectomy alone and laminectomy with instrumented fusion in patients with DCM and found no important differences [ 19 ]. A recent narrative review concluded that conventional laminectomy alone was an effective treatment without the additional risks of posterior instrumentation in highly selected patients with normal preoperative cervical sagittal alignment [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the national Swedish spine registry on patients with CSM, reoperation was estimated to 3.4% after standalone laminectomy and 7.9% after laminectomy and fusion. Five year mortality was estimated to 16.3% in the same population (35) .…”
Section: Sample Size {14}mentioning
confidence: 99%
“…This study is a retrospective post hoc analysis of a previously published cohort of 717 patients surgically treated for DCM with LAM or LAM + F at the 18 major spine centers in Sweden since the registration started in January 2006 until March 2019. The previous study focused on efficacy and cost-effectiveness [8].…”
Section: Participantsmentioning
confidence: 99%
“…Nonetheless, the prognostic implications of these predictors are poorly understood, as is the value of adding a posterolateral instrumented fusion to a laminectomy. Although older studies present high rates of post-laminectomy kyphosis potentially advocating prophylactic fusion [7], modern studies indicate no clinical advantage of adding fusion to laminectomy [8][9][10]. Furthermore, fusion surgery itself may lead as frequently as laminectomy to kyphosis at the proximal or distal junction [11].…”
Section: Introductionmentioning
confidence: 99%